Factors Analysis Affecting Low Productivity in High-Rise Building Projects in Surabaya City - Indonesia, Aileen; Wiguna, I Putu Artama (Journal of Civil Engineering, 2024)
High-rise building construction projects are characterized by significant risks and numerous challenges, which frequently lead to low productivity, causing delays and hindering project completion. One way to address these problems is to analyze the risk factors of low productivity in construction projects using a clustering method based on their probability and impact. This approach helps determine the dominance level of each cluster and provides insights into the occurrence of risk factors that affect low productivity in high-rise building projects in Surabaya City. This research was conducted with surveys filled out by 37 respondents involved in four high-rise building projects in Surabaya City. The aim of this study is to analyze risk factor clustering and determine the dominance of each cluster affecting low productivity in high-rise building projects in Surabaya City by employing the Agglomerative Hierarchical Clustering method to identify clusters and determine the most dominant cluster using Euclidean Distance. From the literature review, 33 risk factors were identified as the variables of this research. The AHC method was carried out based on the mean probability and impact of each cluster obtained from the survey. The result of AHC is that Cluster 1 consists of 23 factors, Cluster 2 consists of 5 factors, and Cluster 3 consists of 5 factors. For the dominance level of each cluster, the Euclidean distance method was carried out, and the result was that Cluster 2 emerged as the highest overall risk, and Cluster 3 represented a low overall risk.